Metroglyph analysis on genetic diversity in germplasm accessions of sunflower (Helianthus annuus L.): METROGLYPH ANALYSIS ON GENETIC DIVERSITY IN GERMPLASM ACCESSIONS OF SUNFLOWER - R CHANDIRAKALA,; AMEENA PREMNATH,; N MANIVANNAN, (Journal of Oilseeds Research, 2015)
Astudyon genetic diversityin sunflower germplasmaccessions was carried out at the Oilseeds farm, Department of Oilseeds, TNAU, Coimbatore, Tamil Nadu. The materials consisted of 46 germplasm accessions collected from the Indian Institute of Oilseeds Research, Hyderabad. Observations on six characters viz., days to 50% flowering, plant height (cm), head diameter (cm), 100-seed weight (g), volume weight (g/100ml) and seed yield/plant (g) were recorded. Metroglyph and index score method was used to assess the genetic variability. All the accessions were grouped into nine groups. Maximum number of genotypes(11) were grouped in group IV followed by group V with nine genotypes. The cluster VIII possessed two accessions with moderate head diameter, 100-seed weight, volume weight and seed yield/plant. The genotypes belonging to the groups II, V and VIII recorded moderate seed yield/plant. The genotypes in the clusters III, VI and IX recorded high seed yield/plant. Highest index score of 16 was observed by GMU 539 in the cluster IX and the accessions GMU 520 in the cluster V and GMU 558 in the cluster IX recorded next highest index score of 15. Findings of the present study suggested that the genotypes having high index scores and belonging to different groups could be utilized in breeding programme to create high variability for various characters.